AESTHETIK VALUABLES AND THEIR ROLE IN EDUCATION OF STUDENTS NOWDAYS - Лагетко, В. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Education aesthetik relation of youth to life foresee their education of relation to nature, to work and also foresee political, moral, religious, physical, art and last sex education therefore aesthetik education is complex syncretic form in education of youth.